(untitled) (Web of Teachers: Inderscience Research, 2025)
Uzbekistan, being an ISO member, has developed a "Program for the Implementation and Development of a Management System Compliant with International Standards," which requires the participation of textile industry enterprises. Transitioning to management based on international standards is a requirement of the modern market. The consumer is now concerned not only with product quality issues: it is important for the modern consumer to know how production affects the environment, and how the issues related to labor protection and employee health are.